Anodic TiO2 nanotube layers: Why does self-organized growth occur-A mini review - Zhou, Xuemei; Nguyen, Nhat Truong; Özkan, Selda; Schmuki, Patrik (Electrochemistry Communications, 2014)
The present review gives an overview of the highlights of more than 10 years of research on synthesis and applications of ordered oxide structures (nanotube layers, hexagonal pore arrangements) that are formed by self-organizing anodization of metals. In particular we address the questions after the critical factors that lead to the spectacular self-ordering during the growth of anodic oxides that finally yield morphologies such as highly ordered TiO2 nanotube arrays and similar structures. Why are tubes and pores formed-what are the key parameters controlling these processes?
EAM Import::2019-03-13